Effects of Arterial Stiffness and Carotid Intima-Media Thickness Progression on the Risk of Overweight/Obesity and Elevated Blood Pressure/Hypertension: a Cross-Lagged Cohort Study. Issue 1 (17th November 2021) - Agbaje, Andrew O.; Barker, Alan R.; Tuomainen, Tomi-Pekka
Abstract : Supplemental Digital Content is available in the text. Abstract : We examined the temporal longitudinal associations of carotid-femoral pulse wave velocity (cfPWV), a measure of arterial stiffness, and carotid intima-media thickness (cIMT) with the risk of overweight/obesity and elevated blood pressure (BP)/hypertension. We studied 3862 adolescents aged 17.7 years from the Avon Longitudinal Study of Parents and Children, followed-up for 7 years. cfPWV and cIMT were measured by ultrasound. Total and trunk fat mass and lean mass were assessed by dual-energy X-ray absorptiometry. Body mass index and BP were measured. Data were analyzed using logistic regression, linear mixed-effect, and cross-lagged structural equation models, with covariate adjustments. Among 1719 male and 2143 female participants, higher cfPWV at 17.7 years was associated with the risk of elevated systolic BP/hypertension (odds ratio, 1.20 [1.02–1.41]; P =0.026), elevated diastolic BP/hypertension (1.77 [1.32–2.38]; P <0.0001), body mass index-overweight/obesity (1.19 [1.01–1.41]; P =0.041), and trunk fat mass overweight/obesity (1.24 [1.03–1.49]; P =0.023) at 24.5 years. Higher cIMT at 17.7 years had no associations with obesity and elevated BP at follow-up. cfPWV progression was directly associated with 7-year increase in systolic BP (effect estimate 16 mm Hg [9–24]; P <0.0001) and diastolic BP (28 mm Hg [23–34]; P <0.0001). cIMT progression was directly associated with the 7-year increase of all adiposity measures and diastolic BP. In the temporal analysis, baseline cfPWV was directly associated with follow-up systolic and diastolic BP, however, baseline BP was unassociated with follow-up cfPWV. cfPWV but not cIMT was bidirectionally associated with adiposity. Obesity and hypertension prevention from adolescence may require developing novel approaches to mitigate arterial stiffness.